Relationship between serum cytokine levels and histopathological changes of liver in patients with hepatitis B - Akpolat, Nusret; Yahsi, Seyfettin; Godekmerdan, Ahmet; Demirbag, Kutbettin; Yalniz, Mehmet (Baishideng Publishing Group Inc, 2005)
AIM: To investigate whether there was a relationship between the liver functions and fibrosis scores of hepatitis B patients and their TNF-alpha, IFN-gamma, IL-4, and TGF-beta(1) serum levels based on the studies of liver biopsies. METHODS: Thirty patients with chronic hepatitis B (CHB) receiving no treatment and 30 healthy individuals with negative hepatitis serology and normal values of liver biochemistry were studied. After serum samples of the patients were collected, liver needle biopsy was performed on each patient. Cytokine levels were studied by ELISA. The biopsy materials were scored based on Knodell's histological activity index. RESULTS: In comparison of cytokine levels between CHB patients and control group, TNF-alpha, IL-4, and TGF-beta(1) levels of the patients were higher in CHB patients than in the controls, while IFN-gamma level was lower in the patients than in the controls. There were significant differences between the groups in TNF-alpha, IL-4, TGF-beta(1), and IFN-gamma (P<0.005, 0.03, 0.002, 0.0001, respectively). There was a negative correlation between TGF-beta(1) and IL-4 and IFN-gamma (P<0.05), TNF-alpha and the other cytokines and IFN-gamma and IL-4 were not correlated (P>0.05). TGF-beta(1) was correlated with fibrosis (P<0.05). Liver necroinflammatory activity and fibrosis and TNF-alpha, IL-4, and IFN-gamma were not correlated (P>0.05). CONCLUSION: In the course of HBV infection and its chronic progress, cytokines play an important role. IL-4 and IFN-gamma are effective in the chronic progression, while TGF-beta(1) is effective in the development of fibrosis. Serum cytokine levels may be effective tools in the estimation of chronic progression and fibrosis development. (C) 2005 The WJG Press and Elsevier Inc. All rights reserved.
Keywords: Hepatitis B; Cytokine